Effect of the Location of the Detonation Initiation Point for Bench Blasting - Liang Liu; Ming Chen; Wenbo Lu; Yingguo Hu; Zhendong Leng (Shock and Vibration)
Uneven floor and fragmentation play an important role in blasting operations due to the direct effects on the efficiency of hauling and loading. This paper focuses on the influences of initiation position on bench blasting in order to improve blasting effects. The numerical simulations of bench blasting at different initiation points (top, middle, and bottom) are implemented based on secondary development of LS-DYNA with a tensile-compressive damage model. The damage spatial distribution characteristics of different initiation points are compared. The outlines of rock foundation and boulder areas are analyzed with the damage threshold of critical breakage that is ascertained by acoustic characteristic of damage rock mass. Results of the numerical simulations demonstrate that different initiation points make a great influence on the stress and energy distribution in blasting process and induce different blasting effects. Middle initiation turns out to be the best initiation to increase the flatness of the floor and decrease the oversize boulder ratio simultaneously, which will increase the damage areas of the bottom and top regions and give a better blasting effect. Field experiment in Baihetan Station was carried out to validate conclusions of numerical simulation. Research could provide a good reference for the improvement of rock blasting.